Zeolite Synthesis and its Application as Adsorbent - Das, Shakti Nath (My University, 2011)
The present environmental concerns over fly ash disposal have sparked a resurgent interest in its conversion to value added product such as zeolites. Fly ash derived from coal residues has a tremendous potential for conversion to zeolites. Still more remarkable is the subsequent utilization of theses zeolites synthesized from fly ash as adsorbent for removal of dye in the industry. In the present study the coal based fly ash was used to synthesis X-type and A-type zeolite by alkali fusion, followed by hydrothermal treatment. The synthesized zeolite was then characterized using various techniques such as X-ray diffraction (XRD), Scanning Electron Microscopy (SEM). Particle Size, surface area and pore volume of the synthesized zeolites were also being measured. The synthesized zeolite was then used as adsorbent for removal of different dyes such as methyl orange, methylene blue and safranine T from the aqueous solution. Dyestuff production units and dyeing units have always had a pressing need for techniques that allow economical pre-treatment for colour in the effluent. At present, there is a growing interest in using low-cost, commercially available materials for the adsorption of dyes. Zeolite synthesized from fly ash was found to be a good adsorbent for removal of Methylene blue, Methyl Orange and Safranine T. Various types of materials such as silica gel, alumina, bentonite, perlite and clays have already been used as adsorbent to removal of these dyes. Zeolites are interesting materials because of their intrinsic properties to removal of these dyes. The adsorption of basic and acid dyes from aqueous solution onto zeolite synthesized from fly ash has been studied using an agitated batch adsorber. Physical regeneration of used adsorbent was studied at higher temperature. Combustion at higher temperature produced effective adsorbents for further adsorption. Several factors have been studied: initial dye concentration, adsorbent mass and contact time. For adsorption of methyl orange experimenal data was fitted to the Freundlich isotherm better than Langmuir isotherm. Correlation coefficient was found to be 0.998.
M.Tech. (Chemical Engineering)
Keywords: Zeolite; Adsorption